Challenges of Deliberation and Participation - Forester, John (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2006)
The future of sustainability is tied to the future of our ability to manage interconnectedness and interdependence, and thus to our abilities to engage in cooperative, value-creating public deliberations and negotiations. To understand these issues, we need a better understanding of the micro-politics of planning and public participation, the relationships between our received theories and our practices, and in particular, the work of public dispute resolution and its implications for democratic deliberation and governance. We need better to understand the differences between dialogue, debate, and negotiation, as well as the corresponding work of facilitating a dialogue, moderating a debate, and mediating an actual negotiation. Contrasting processes and practical attitudes of dialogue, debate, and negotiation can teach us, in the context of creating a sustainable future, that we must devise discursive and conversational political processes and institutions that explore possible commitments so that we not only know the right things to do but actually bring ourselves and one another to do those right things.